2022
DOI: 10.3390/antibiotics11111631
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling, In Vitro Antimalarial Investigation and In Silico Modeling of the Marine Actinobacterium Strain Rhodococcus sp. UR111 Associated with the Soft Coral Nephthea sp.

Abstract: Malaria is a persistent illness with a great public health concern. To combat this fatal disease, developing effective antimalarial medications has become a necessity. In the present study, we described the actinomycetes associated with the Red Sea soft coral Nephthea sp. and isolated a strain that was sub-cultured in three different media (M1, ISP2, and OLIGO). Actinomycete isolate’s phylogenetic analysis of the 16S rRNA gene revealed that it belongs to the genus Rhodococcus. In vitro screening of the antimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, the focus on target-based drug discovery and finding targeted antimalarial drugs that treat all stages of the disease became a need. Previously published data revealed the presence of various malarial targets that affects different stages of parasite infection [8], among them, lysyl-tRNA synthetase, [38] which is an enzyme central to protein translation and responsible for protein formation [39]. Earlier studies revealed that lysyl-tRNA synthetase could be considered as an attractive, druggable, antimalarial target that can be selectively inhibits protein synthesis and prevents liver and blood-stage proliferation [34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the focus on target-based drug discovery and finding targeted antimalarial drugs that treat all stages of the disease became a need. Previously published data revealed the presence of various malarial targets that affects different stages of parasite infection [8], among them, lysyl-tRNA synthetase, [38] which is an enzyme central to protein translation and responsible for protein formation [39]. Earlier studies revealed that lysyl-tRNA synthetase could be considered as an attractive, druggable, antimalarial target that can be selectively inhibits protein synthesis and prevents liver and blood-stage proliferation [34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…All media were supplemented with 0.2 µm pore size filtered cycloheximide (100 µg/mL), nystatin (25 µg/mL) and nalidixic acid (25 µg/mL) to facilitate the isolation of slow-growing actinobacteria. Cycloheximide and nystatin inhibit fungal growth, while nalidixic acid inhibits many fast-growing Gram-negative bacteria [ 8 ]. All media contained Difco Bacto agar (18 g/L) and were prepared in 1 L artificial sea water (NaCl 234.7 g, MgCl 2 .6 H 2 O 106.4 g, Na 2 SO 4 39.2 g, CaCl 2 11.0 g, NaHCO 3 1.92 g, KCl 6.64 g, KBr 0.96 g, H 3 BO 3 0.26 g, SrCl 2 0,24 g, NaF 0.03 g and ddH 2 O to 10.0 L).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the antiplasmodial effect of isolated compounds in vitro, the Malstat assay was used as described [ 60 ]. To synchronize the culture of the Plasmodium NF54 strain, parasites with many ring stages were centrifuged, and the pellet was resuspended in the five-fold pellet volume of 5% w/v sorbitol /distilled H 2 O and incubated for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The steps are chosen based on the study type (untargeted vs. targeted), the sample type (solids, liquids), the separation apparatus (GC, LC), and the detection method (MS, IR, NMR). [30][31][32][33]…”
Section: Methodsmentioning
confidence: 99%